Review on polymer composites with high thermal conductivity and low dielectric properties for electronic packaging. (January 2022) - Li, R.; Yang, X.; Li, J.; Shen, Y.; Zhang, L.; Lu, R.; Wang, C.; Zheng, X.; Chen, H.; Zhang, T.
Abstract: Polymers are widely used in electronic packaging due to their easy processing, lightweight, excellent insulation, and good mechanical properties. However, as electronic devices gradually turn towards high energy density and low signal delay, polymers with high thermal conductivity and low dielectric properties are in large demand. Since polymers have low intrinsic thermal conductivity, thermally conductive fillers need to be added when preparing polymer composites. However, there is always a trade-off between the thermal conductivity and the dielectric properties in polymer composites, which is significant for researchers to understand. Therefore, for the first time, this review elaborates how to balance the high thermal conductivity and the low dielectric properties. Recent progress of thermally conductive fillers is summarized, aiming to provide a reference for applying polymer composites in the field of microelectronics. Also, the challenges and the outlooks of polymers with high thermal conductivity and low dielectric properties are outlined. Graphical abstract: Image 1 Highlights: Thermally conductive and dielectric polymer composites (TDPCs) for electronic packaging are summarized. TDPCs are divided into three parts: the single fillers, hybridization and a 3-dimensional thermally conductive network. This work provides design strategies for both high thermal conductivity and low dielectric properties in polymers.